Data Sheet 1_Transcultural adaptation and psychometric evaluation of the Chinese version of attitude and confidence with oral healthcare among nursing students scale: a cross-sectional survey in China.pdf - Yaqin Li (2094049) (2025)
Objective Positive attitudes and strong confidence toward oral healthcare among nursing students are essential prerequisites for providing quality oral healthcare, which directly impacts the likelihood and effectiveness of their post-training care practices. However, no validated scale is currently available in China to measure nursing students’ attitudes toward oral healthcare and confidence. This study aims to adapt the original English version of the attitude and confidence with oral healthcare among nursing students (ACORN) scale into Chinese culture and assess its psychometric properties. Methods This study followed the Brislin Translation Model, including forward translation, back translation, and expert consultation (consultation of the differences between the original English version and the synthesized back-translated version of the ACORN scale with the original author, pilot testing, expert consultation, and bilingual testing). The formal experiment was conducted across eight universities offering bachelor’s nursing programs in China (Chengdu and Shenyang City), involving 536 nursing students who had completed oral healthcare courses. Item analysis, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and reliability testing (internal consistency and test–retest reliability) were conducted. The data were divided into two equal sets using the random number table function in SPSS, one for EFA and the other for CFA. Results The EFA extracted three dimensions: attitudes toward oral care (8 items), confidence in oral care practices (4 items), and confidence in diagnosing oral diseases (10 items), with a cumulative variance contribution rate of 66.33%. The CFA confirmed the three-factor structure with excellent model fit indicators. The overall Cronbach’s alpha for the Chinese version of the ACORN scale was 0.95, with the three dimensions having values of Cronbach’s alphas of 0.92, 0.85, and 0.94, respectively. Twenty nursing students participated in a test–retest survey after a two-week interval, resulting in a test–retest value of 0.76. Conclusion The Chinese version of the ACORN scale exhibits strong reliability and validity performances and can be used to assess the oral care-related attitudes and confidence of nursing students in China.